The effect of workpiece cooling on the machining of biomedical grade polymers - ALDWELL, BARRY; O'DONNELL, GARRET (My University, 2014)
Biomedical grade polymers are commonly used in applications where surface finish and dimensional accuracy are key, such as in t otal joint replacement and intraocular lenses, yet relatively little research has been conducted into the machining of these materials. It has been established that workpiece temperature has a lar ge effect on machinability in soft polymers , with alterations to the chip formation mechanism p ossible when workpiece temperature is adequately controlled. This is due to the change in material behaviour at the glass tran sition temperature, which varies with the composition and crystallinity of the polymer. In polymers which have low glass transition te mperatures, liquid nitrogen cooling is used, in some cases with a control system used to regulate the workpiece temperature during machinin g. This work concentrates on the machining of Ultra High Molecular Weig ht Polyethylene (UHMWPE) workpieces which have been pre - cooled before mach ining. Past work has concentrated on the development of a measurement chain for the monitoring of polymer machining, and characterising the machining of UHMWPE at ambient temperature, wh ile varying tool and process parameters. Little work has been done on the cryogenic machining of UHMWPE, though it is known that the hi gh crystallinity of UHMWPE alters thermomechanical behaviour w hen compared to conventional blends of polyethylene, and the glass transition temperature is in the region of - 120°C. The aim of this work is to p rovide insight into the effect of workpiece temper ature on machinability and surface quality in UHMWPE.
9th CIRP Conference on Intelligent Computation in Manufacturing Engineering
PUBLISHED
Keywords: Polymer; Machining; Cryogenic